تقويم برنامج ترقية مهارات اللغة العربية في مجموعة الكندي في جامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج - Wahhab, Abdul; Sari, Devi Rafika; Qomari, Nur (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2023)
In the academic world, mastering a foreign language is very important. Al-Kindy Community is a community to hone Arabic language skills for students majoring in Arabic Language Education. As a community for improving Arabic language skills that exists at universities, researchers are interested in analyzing the activity programs that exist in the Al-Kindy community. This research aims first, to find out the objectives of the Al-Kindy program. Second, knowing the implementation of the al-Kindy program. Third, know for evaluating the al-Kindy program. The method used in this research is a qualitative and quantitative combined method with using likert scale. The data collection techniques used in this research are interviews and documentation. The research results show first are, the general goals of the al-Kindy program is to improve students' Arabic language skills and take part in every Arabic language competition for student level. Second, the implementation of the al-Kindy program includes activities carried out every weekend on campus which are guided by experienced Al-Kindi lecturers and alumni. Third, the results of the evaluation conducted by researchers on the skills improvement program at Al-Kindy showed a percentage of 84%, which means very good.